PREVENTION OF EMERGENCIES IN THE REPUBLIC OF UZBEKISTAN AND THE STAGES OF DEVELOPMENT AND PROBLEMS OF IMPROVEMENT OF THE STATE SYSTEM TO ACT IN SUCH SITUATIONS - TURSUNOV ABDUMANSUR ABDUAZIZOVICH; RAZZAKOV HASANBOY MIRZAEVICH (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article describes the stages of formation of the FVDT system for the protection of the population and the territory from emergencies, the consequences of emergencies, the stages and processes of reforms, as well as the prospects for further improvement of the system.